The value of G-CSF in women experienced at least one implantation failure: a systematic review and meta-analysis - Su, Qing; Pan, Zhuo; Yin, Rong; Li, Xuemei (Frontiers in Endocrinology, 2024)
Objective Despite the developments of in vitro fertilization (IVF) protocols, implantation failure remains a challenging problem, owing to the unbalance between the embryo, endometrium, and immune system interactions. Effective treatments are urgently required to improve successful implantation. Recently, many researchers have focused on granulocyte colony-stimulating factor (G-CSF) to regulate immune response and embryo-endometrium cross-talk. However, previous studies have reported inconsistent findings on the efficacy of G-CSF therapy on implantation failure. The objective of this review was to further explore the effects of G-CSF according to administration dosage and timing among women who experienced at least one implantation failure. Methods We systematically searched MEDLINE, Embase, the Cochrane Central Register of Controlled Trials, Scopus, and Web of Science for randomized controlled trials of G-CSF on implantation failure up to July 21, 2023. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated and the heterogeneity of the studies with the I2 index was analyzed. Results We identified a total of 2031 studies and finally included 10 studies in the systematic review and meta-analysis. G-CSF administration improved the clinical pregnancy rate (CPR), implantation rate (IR), biochemical pregnancy rate (BPR), and live birth rate (LBR) in women with at least one implantation failure. Subgroup analyses showed that G-CSF treatment could exert good advantages in improving CPR [OR=2.49, 95%CI (1.56, 3.98), I2 = 0%], IR [OR=2.82, 95%CI (1.29, 6.15)], BPR [OR=3.30, 95%CI (1.42, 7.67)] and LBR [OR=3.16, 95%CI (1.61, 6.22), I2 = 0%] compared with the blank control group. However, compared with placebo controls, G-CSF showed beneficial effects on CPR [OR=1.71, 95%CI (1.04, 2.84), I2 = 38%] and IR [OR=2.01, 95%CI (1.29, 3.15), I2 = 24%], but not on LBR. In addition, >150μg of G-CSF treatment increased CPR [OR=2.22, 95%CI (1.47, 3.35), I2 = 0%], IR [OR=2.67, 95%CI (1.47, 4.82), I2 = 0%] and BPR [OR=2.02, 95%CI (1.17, 3.47), I2 = 22%], while ≤150μg of G-CSF treatment improved miscarriage rate (MR) [OR=0.14, 95%CI (0.05, 0.38), I2 = 0%] and LBR [OR=2.65, 95%CI (1.56, 4.51), I2 = 0%]. Moreover, G-CSF administration on the day of embryo transfer (ET) could increase CPR [OR=2.81, 95%CI (1.37, 5.75), I2 = 0%], but not on the day of ovum pick-up (OPU) or human chorionic gonadotropin (HCG) injection. Conclusion G-CSF has a beneficial effect on pregnancy outcomes to some extent among women who experienced at least one implantation failure, and the administration dosage and timing influence the effect size. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023447046.